PENGARUH GREEN MARKETING, KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PRODUK GARNIER PEMBERSIH WAJAH (STUDI PADA PELANGGAN DI KOTA SURABAYA) - azzahra, Nastasya; Nurhadi (FEB Universitas Sam Ratulangi Manado, 2024)
This research aims to analyze the influence of green marketing, product quality and customer satisfaction on customer loyalty for Garnier facial cleanser products in the city of Surabaya. The population of this study are customers who have used or repurchased Garnier facial cleansing products more than once. The sample used was 150 respondents using purposive sampling technique. The data collection technique uses the questionnaire distribution method. And the data was processed using SPSS with the multiple linear regression analysis testing method. The results of the F test show that simultaneously the independent variables green marketing, product quality and customer satisfaction have a significant effect on customer loyalty. Meanwhile the t test results show empirical evidence that; a) partially the green marketing variable (X1) and customer satisfaction variable (X3) have a positive and significant effect on customer loyalty (Y); b) partially the product quality variable (X2) has a positive but not significant effect on customer loyalty (Y).